Friction properties of SLM formed Ti48Al2Cr2Nb alloy - Zhanyong Zhao; Yongli Guo; Wenbo Du; Peikang Bai; Zhen Zhang; Liqing Wang; Kai Ma; Yaohao Du (Advanced Manufacturing)
Ti48Al2Cr2Nb alloy was prepared by selective laser melting (SLM). The effects of different rotational speeds on the friction properties of Ti48Al2Cr2Nb alloy and the alloy after hot isostatic pressing (HIP) were studied. The results are as follows: (1) With the increase of rotational speeds, the wear rate of Ti48Al2Cr2Nb alloy decreases and the friction coefficient decreases gradually. This is due to the formation of a mechanical mixed layer, which reduces the contact area between the friction material and the wear surface and improves the tribological properties. (2) After HIP treatment, the wear rate is greatly reduced, and some large flake wear debris appear on the wear surface. This is because the hardness of the material after HIP treatment becomes larger, and it has strong wear resistance and cutting resistance. However, the crystal structure inside is dense and orderly, and it is difficult to deform plastically, which is prone to brittle fracture. (3) When the rotational speeds is 400 r/min, the friction coefficient is the lowest. The reason is that the sample has low hardness and good plasticity. At high speeds, the material will deform, plastic flow and disperse mixing, forming a large number of thick mechanical mixing layers.